INVESTIGATION OF THE RISKS OF INTRODUCING PRODUCED WATER INTO FRESHWATER INJECTION SYSTEM - Usman Usman (Testing Center for Oil and Gas LEMIGAS, 2015)
Mixing of waters from different sources may exacerbate the risk of formation damage and can impactÂ on oil recovery. A case study is presented to demonstrate how to assess these risks. The study relies onÂ laboratory-based work. Appropriate materials, methods, and procedures to assure the quality of test dataÂ and derive technically valid risks potential interpretations are discussed. The risks for potential plugging, scaling, permeability reduction, and oil recovery loss caused by introducing produced water are identified. Plugging is caused by bacterial growth and solid particles present in produced water. Bacterial growth is categorized as high. Solids Concentration is also high with its mean diameter larger than the non-damaging particle size. The CaCO3 scale is likely at reservoir temperature due to high concentration of HCO-3 in the produced water. Mixing of untreated produced water and treated freshwater caused signifi- cantly reduction in permeability. For the 25% PW and 75% FW mix, the permeability decreases by about 80% of its initial permeability. Adding 2000 ppm of biocide and fi ltered using 11 micron filter paper improved the quality of produced water. For the same mixing fraction, the permeability decreases only 47%. Analysis of pore throat size in conjunction with particle size of water samples suggests the need for using a fi lter less than 11 micron to avoid permeability decline imposed by solid particles. Waterflood experiments showed an ultimate recovery factor of 46.1% of original oil in place obtained from freshwater injection. Introducing 50% of produced water caused an oil recovery loss of 16% compared to freshwater injection alone. This lost oil recovery represents a quantitative effect of formation damage on oil production and may be valuable from the economic viewpoint.